The Relationship between Working Parents’ Parenting Patterns and Children’s Independence in Kindergarten in Nagari Lubuk Malako, Sangir Jujuan District, South Solok Regency - Widia Rahmawati; Syahrul Ismet (Darul Yasin Al Sys, 2026)
Children’s independence is an essential developmental aspect of early childhood education because it reflects their ability to manage themselves, complete simple tasks, and assume responsibilities appropriate to their developmental stage. This study aims to examine the relationship between working parents’ parenting patterns and children’s independence in kindergartens in Nagari Lubuk Malako, Sangir Jujuan District, South Solok Regency. A quantitative approach with a descriptive correlational method was employed. The population comprised 112 parents of kindergarten children from TK Annur Koto Tuo Lubuk Malako, TK Raudhatul Ilmi Koto Gadang, and TK Kasih Bunda, with 53 respondents selected through purposive sampling. Data were collected using a closed-ended questionnaire based on indicators of parenting patterns and children’s independence and were analyzed using descriptive statistics and Pearson product–moment correlation with SPSS. The findings indicate a relationship between working parents’ parenting patterns and children’s independence. The R² value of 0.206 shows that parenting patterns accounted for 20.6% of the variance in children’s independence, while the remaining 79.4% was influenced by other factors. This study concludes that consistent, communicative, and democratic parenting plays an important role in supporting children’s independence. These findings contribute to early childhood education by emphasizing the relevance of parenting quality in fostering children’s autonomy and responsibility during the kindergarten stage.